The Potential Advantages Of Utilizing Venacular Language In Early Education In Papua As A Bridge To The Indonesian National Educational System - Leonard Sumule; Agam Iheanyi-Igwe (International Journal of Indonesian Philosophy & Theology, 2020)
This paper discusses the potential advantages of using vernacular language instruction to address  the high drop out rates of indigenous elementary students in Highlands Papua, Indonesia. The effect of challenges created by differences between local culture and the culture presented in the national Indonesian educational system is discussed. David Kolb’s Experiential Learning theory is discussed as a method that can improve student outcomes by encouraging early comprehension through linguistically and culturally relevant experiences. Successful bilingual primary education programs in various countries are discussed. Examples are presented that illustrate the importance and advantages of foreigners acknowledging local language and culture while amongst the Papua people. This paper proposes steps that the Indonesian government, especially the local jurisdiction of Papua province’s governance, can take to utilize vernacular language to address the achievement gap of indigenous elementary students in Highlands Papua.